The unethical behaviours among practitioners in project management stages in Klang Valley construction projects - Hafez, Fatma Alzahraa, Sami Mohamed (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2020)
The main aim of this study is to examine the unethical behaviours among the practitioners in project management stages in Klang Valley construction projects. The objectives of this thesis are as follows: Firstly, to identify the factors that drive the practitioners to unethical behaviours in project management stages. Secondly, to identify the unethical behaviours that occur in the project management stages. Thirdly, to evaluate the level of awareness and application of the principles of the code of ethics when the practitioners carry out their duty in the projects. Fourthly, to develop the practical guidelines for managing and reducing the unethical behaviours in construction projects. However, it appears that practitioners in the building construction industry deemed to behave unethically when implementing project management on various stages that persist to lead to lower outcomes in project quality. This negative impact can damage the outcomes of economic and social development, which may also stop the sustainable development. The methodology adopted in this study was quantitative approach through literature reviews followed by the questionnaire to collect the required data from the practitioners. The respondents comprised of 336 practitioners from Board of Architects, Engineers and Quantity Surveyors. A pilot study was conducted to ensure validity of the research by fifty practitioners, who are from different fields (Engineers, Quantity Surveyors, and Architects) in Klang Valley. The data were analysed using descriptive and inferential statistics such as one-way ANOVA and Multiple Linear Regression (MRA). The results showed that project factors have the highest mean among the factors that drive the practitioners to unethical behaviours in project management stages followed by external environment, personal environment, individual attributes, work environment, professional environment, governmental environment, and social environment has the lowest mean. Based on MRA results, unethical behaviours were significantly by three of the eight factors, namely project factors, personal environment and lastly external environment. Regarding the unethical behaviours in the project management stages, the fifth stage has the highest mean as the most occurred unethical behaviours, followed by stage two. On the other hand, stage three showed the lowest mean among other stages, this followed by stage four as the second lowest mean. Concerning the level of awareness and applying the principles of the code of ethics, honesty and reliability came as the highest principles of the code of ethics, followed by integrity, fair reward, objectivity, fairness, and accountability. In this regard, based on One-way ANOVA results, differences were found on honestly and fairness based on the respondents' years of experience. However, no differences in the principles of the code of ethics were found on the respondents' level of education. There are series of efforts should be made early in the life of the practitioner such as creating awareness, education, training, cancellation of license on repetitive violations, heavier penalties, and quality assurance group should be part of every project stage to ensure quality along with a project to prevent unethical behaviours in project management stages.